Disruption of de novo fatty acid synthesis via acetyl‐CoA carboxylase 1 inhibition prevents acute graft‐versus‐host disease. Issue 9 (18th July 2016) - Raha, Solaiman; Raud, Brenda; Oberdörfer, Linda; Castro, Carla N.; Schreder, Alina; Freitag, Jenny; Longerich, Thomas; Lochner, Matthias; Sparwasser, Tim; Berod, Luciana; Koenecke, Christian; Prinz, Immo
Abstract : In an experimental model for acute graft‐versus‐host disease we show that donor T‐cell‐specific deficiency in acetyl‐CoA carboxylase 1 (TACC1) protects recipient mice after allogeneic stem cell transplantation. Our results suggest that de novo fatty acid synthesis might be a promising target for prevention and treatment of acute graft‐versus‐host disease. Abstract : Upon antigen‐specific or allogeneic activation, T cells sharply increase their metabolic activity to cope with augmented needs for proliferation and effector functions. Therefore, enzymes involved in energy metabolism constitute attractive targets to modulate the activity of pathogenic effector T cells in the setting of graft‐versus‐host‐disease (GVHD). Here, we show that T cells deficient for acetyl‐CoA carboxylase 1 (TACC1) are dramatically less pathogenic than wild‐type (WT) T cells in a lethal C57BL/6 into BALB/c model of acute GVHD and permitted sustained survival of recipient mice. In line with this clinical observation, higher frequencies of GVHD‐suppressing Foxp3 + regulatory T (Treg) cells were detected in the colon of TACC T‐cell recipients. In vitro, T‐cell stimulation with allogeneic DCs induced higher proportions of Treg cells but also led to diminished proliferation of TACC1 T cells compared to WT T cells. Furthermore, TACC1 T cells activated by allogeneic DCs showed impaired glycolysis and lipid synthesis. Thus, targeting de novo fatty acid synthesis via acetyl‐CoA carboxylase inhibition may be a promising new strategy to prevent GVHD.